조건부 생성모델을 이용한 강수 패턴에 따른 지하수위 생성 및 이의 활용에 관한 연구 - 정지호(Jiho Jeong); 정진아(Jina Jeong); 이병선(Byung Sun Lee); 송성호(Sung-Ho Song) (자원환경지질, 2021)
In this study, a method has been proposed to improve the performance of hydraulic property estimation model developed by Jeong et al. (2020). In their study, low-dimensional features of the annual groundwater level (GWL) fluctuation patterns extracted based on a Denoising autoencoder (DAE) was used to develop a regression model for predicting hydraulic properties of an aquifer. However, low-dimensional features of the DAE are highly dependent on the precipitation pattern even if the GWL is monitored at the same location, causing uncertainty in hydraulic property estimation of the regression model. To solve the above problem, a process for generating the GWL fluctuation pattern for conditioning the precipitation is proposed based on a conditional variational autoencoder (CVAE). The CVAE trains a statistical relationship between GWL fluctuation and precipitation pattern. The actual GWL and precipitation data monitored on a total of 71 monitoring stations over 10 years in South Korea was applied to validate the effect of using CVAE. As a result, the trained CVAE model reasonably generated GWL fluctuation pattern with the conditioning of various precipitation patterns for all the monitoring locations. Based on the trained CVAE model, the low-dimensional features of the GWL fluctuation pattern without interference of different precipitation patterns were extracted for all monitoring stations, and they were compared to the features extracted based on the DAE. Consequently, it can be confirmed that the statistical consistency of the features extracted using CVAE is improved compared to DAE. Thus, we conclude that the proposed method may be useful in extracting a more accurate feature of GWL fluctuation pattern affected solely by hydraulic characteristics of the aquifer, which would be followed by the improved performance of the previously developed regression model. 본 연구에서는 Jeong et al. (2020)의 연구에서 수행된 지하수위 변동 패턴의 저차원 특징추출 과정의 문제점을 분석하고, 이에 대한 개선방안이 제안된다. 해당 연구에서는 Denoising autoencoder (DAE)를 이용해 전국의 연 단위 지하수위 변동 자료로부터 저차원 특징이 추출되며, 추출된 자료를 이용해 대수층의 수리 특성값을 예측하는 회귀 모델이 개발되었다. 그러나 특정 지역의 연도별 강수 패턴이 달라질 경우, 지하수위 변동 패턴 및 저차원 특징 또한 달라지며, 이에 따라 동일 지역임에도 불구하고 저차원 특징으로부터 추정되는 수리 특성값이 다양하게 나타날 수 있다. 이러한 문제를 해결하기 위해, 본 연구에서는 조건부 생성 모델인 Conditional variational autoencoder (CVAE)를 이용하였으며, 전국 71개 지역에서 10년 동안 획득된 지하수위 자료와 강수 자료 간 상관관계가 학습되었다. 학습된 모델을 통해 모든 지역에 대해 동일 강수 조건이 적용될 때의 지하수위 자료가 생성되었으며, 생성된 지하수위 자료로부터 저차원 특징이 추출되었다. CVAE를 이용해 동일 강수 조건으로 생성된 지하수위 자료의 저차원 특징과 기존 DAE를 통해 추출된 저차원 특징이 비교되었으며, 그 결과 CVAE를 이용해 추출된 저차원 특징 간 거리가 저차원 공간상에서 보다 가깝게 분포하는 것이 확인되었다. 따라서 제안된 방법을 이용할 경우 대수층 특성에만 영향을 받는 지역별 지하수위 자료 및 저차원 특징이 효과적으로 추출될 수 있으며, 이를 통해 기존 개발된 회귀 모델의 성능이 개선될 수 있을 것으로 판단된다.